Selected Hagiographical and Biblical References in the Corpus of Short Narrative Texts of the Newspaper Besednik - Bošnjak, Blanka (Slavia Centralis, 2023)
In the secularised literary treatment of short narrative texts, the biblical and hagiographical references that will be discussed in this paper appear, inter alia, in the form of allusive implicit references to persons or events from the biblical and hagiographical traditions, due to the educational-didactic concept of the 19th century, when the Besednik newspaper began to appear as a supplement to the publications issued by the Mohorjeva družba publishing company. An examination and analysis of the short narrative texts of the Besednik newspaper, subtitled as “a short and informative newspaper for the Slovene people” published in Klagenfurt between 1869 and 1878 revealed that allusions to biblical and hagiographical contexts appear as quotation figures in the form of intertextual references.
Keywords: Slovenian short narrative prose, the newspaper Besednik (1869– 1878), hagiographical references, biblical references, allusions